Development of Catholic Religious Learning Media for Elementary School Students in Palangkaraya - Paulina Maria Ekasari Wahyuningrum; Irene Hartutik (Graduate Program Magister Manajemen Pendidikan, 2022)
This research aims to develop Catholic religious learning media for elementary school students in Palangka Raya. The learning media developed as illustrated storybooks with 3 themes based on the teacher's textbook: students, society and church. This research is a research and development with development steps from the Dick and Carey model. The subjects of this study were elementary school students taken from 3 schools in Palangka Raya city. Researchers used expert validation from 2 material experts, 1 linguist and small class trials to determine the feasibility of the media. The data analysis technique uses the PSA percentage formula. Based on the score obtained from validator 1, the average assessment score is 85.7%. Based on the scores obtained from validator 2, the average assessment score is 88.7%. Based on the score obtained from validator 1, the average assessment score is 83.3%. From the feasibility study results, material experts and linguists have tested the development of teaching media through storybook products with excellent and feasible results.